2005
DOI: 10.1021/ja0512576
|View full text |Cite
|
Sign up to set email alerts
|

Designed Ferromagnetic, Ferroelectric Bi2NiMnO6

Abstract: A newly designed ferromagnetic, ferroelectric compound, Bi(2)NiMnO(6), was prepared by high-pressure synthesis at 6 GPa. The crystal structure, as determined by synchrotron X-ray powder diffraction, is a heavily distorted double perovskite with Ni(2+) and Mn(4+) ions ordered in a rock-salt configuration. The presence of 6s(2) lone pairs of Bi(3+) ions and the covalent Bi-O bonds give ferroelectric properties with T(CE) of 485 K, while -Ni(2+)-O-Mn(4+)-O-Ni(2+)- magnetic paths lead to a ferromagnetism with T(CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
297
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(316 citation statements)
references
References 24 publications
16
297
2
Order By: Relevance
“…Azuma et el. reported that the C2 symmetry of this compound allows a spontaneous polarization along the b axis, and a calculation Downloaded by [East Carolina University] at 19:07 04 January 2013 assuming a pointcharge model with the above structural parameters gave a polarization of 20 µC/cm 2 [11]. But the observed polarization is much smaller than the calculated value, because the observed ferroelectric polarization should be a projection along the out-of plane direction.…”
Section: Results and Disscussionmentioning
confidence: 83%
“…Azuma et el. reported that the C2 symmetry of this compound allows a spontaneous polarization along the b axis, and a calculation Downloaded by [East Carolina University] at 19:07 04 January 2013 assuming a pointcharge model with the above structural parameters gave a polarization of 20 µC/cm 2 [11]. But the observed polarization is much smaller than the calculated value, because the observed ferroelectric polarization should be a projection along the out-of plane direction.…”
Section: Results and Disscussionmentioning
confidence: 83%
“…The corresponding permittivity is found to be in the range of that reported for BNMO bulk materials. 3 In the high-frequency range, we can also observe a small but perceptible ε (ν) dependence [ Fig. 2(a)], which is at odds with the response of an ideal dielectric, but it is commonly observed in most dielectrics and attributed to the frequency-dependent ac conductivity σ ac .…”
Section: Resultsmentioning
confidence: 88%
“…In contrast, in bulk BNMO, dielectric permittivity was found to be roughly constant (ε ≈ 200) for temperatures well below T F E . 3 Here, we report on a quantitative study of the apparent temperature-dependent dielectric relaxation of BLNMO thin films, which we prove is driven by the temperature dependence of the resistivity instead of the dielectric relaxation of electric dipoles. Impedance spectroscopy methods 10,12,20 have been used to disentangle extrinsic contributions to the measured permittivity and to extract the temperature dependence of the intrinsic dielectric and resistive properties of (Bi 0.9 La 0.1 ) 2 NiMnO 6 films.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Finally, let us point out, for completeness, that the magnetic order parameter transforming as the mS 2 irreducible representation does not form a third power invariant with the mR + 4 ⊗ 2 product. The mS 4 representation does form such invariant and provides coupling, when the spins, in the primary G-type configuration, are along the orthorhombic a o axis. The latter situation is, however, unfavorable for the part of the antisymmetric exchange associated with the octahedral tilting, as discussed in the main text.…”
Section: Discussionmentioning
confidence: 99%